15.34% efficiency all-small-molecule organic solar cells with an improved fill factor enabled by a fullerene additive. Issue 7 (4th June 2020) - Hu, Dingqin; Yang, Qianguang; Chen, Haiyan; Wobben, Friso; Le Corre, Vincent M.; Singh, Ranbir; Liu, Tao; Ma, Ruijie; Tang, Hua; Koster, L. Jan Anton; Duan, Tainan; Yan, He; et al.
Abstract : A fullerene additive adjusts the miscibility between donor and acceptor for morphology optimization and reduces bimolecular recombination, assisting significant improvement of fill factor and efficiency. Abstract : Solution processed organic solar cells (OSCs) composed of all small molecules (ASM) are promising for production on an industrial scale owing to the properties of small molecules, such as well-defined chemical structures, high purity of materials, and outstanding repeatability from batch to batch synthesis. Remarkably, ASM OSCs with power conversion efficiency (PCE) beyond 13% were achieved by structure improvement of the electron donor and choosing Y6 as the electron acceptor. However, the fill factor (FF) is an obstacle that limits the further improvement of the PCE for these ASM OSCs. Herein, we focus on the FF improvement of recently reported ASM OSCs with BTR-Cl :Y6 as the active layer by miscibility-induced active layer morphology optimization. The incorporation of fullerene derivatives, which have good miscibility with both BTR-Cl and Y6, results in reduced bimolecular recombination and thus improved FF. In particular, when ca. 5 wt% of PC71 BM was added in the active layer, a FF of 77.11% was achieved without sacrificing the open circuit voltage ( V OC ) and the short circuit current density ( J SC ), leading to a record PCE of 15.34% (certified at 14.7%) for ASM OSCs. We found that the optimized device showed comparable charge extraction, longer charge carrier lifetime, and slower bimolecular recombination rate compared with those of the control devices (w/o fullerene). Our results demonstrate that the miscibility driven regulation of active layer morphology by incorporation of a fullerene derivative delicately optimizes the active layer microstructures and improves the device performance, which brings vibrancy to OSC research.